Rare and unique adaptations to cancer in domesticated species: An untapped resource?. (29th January 2020) - Thomas, Frédéric; Giraudeau, Mathieu; Dheilly, Nolwenn M.; Gouzerh, Flora; Boutry, Justine; Beckmann, Christa; Biro, Peter A.; Hamede, Rodrigo; Abadie, Jerome; Labrut, Sophie; Bieuville, Margaux; Misse, Dorothée; et al.
Abstract: Strong and ongoing artificial selection in domestic animals has resulted in amazing phenotypic responses that benefit humans, but often at a cost to an animal's health, and problems related to inbreeding depression, including a higher incidence of cancer. Despite high rates of cancer in domesticated species, little attention has been devoted to exploring the hypothesis that persistent artificial selection may also favour the evolution of compensatory anticancer defences. Indeed, there is evidence for effective anti‐cancer defences found in several domesticated species associated with different cancer types. We also suggest that artificial selection can favour the "domestication" of inherited oncogenic mutations in rare instances, retaining those associated to late and/or less aggressive cancers, and that by studying these seemingly rare anticancer adaptations, novel cancer treatments may be found.